Knowledge, Attitude, and Practice (KAP) of School Teachers regarding Epilepsy and their Impact on Student Dropout and Learning in Jammu and Kashmir (J&K), India - Ahad , Amjid (International Journal of Rehabilitation and Special Education (IJRSE), 2025)
Background: Epilepsy, a chronic neurological condition affecting millions worldwide, presents unique educational and social challenges, particularly in regions with limited awareness and Institutional support. These challenges are exacerbated by stigma, misconceptions, and systemic gaps in addressing the needs of students with epilepsy. Objectives: To assess the knowledge, attitudes, and practices of the school teachers in J&K, the northern-most region of India, towards students with epilepsy and identify barriers to inclusive education. Methods: A cross-sectional study was conducted among 550 school teachers in the J&K Union Territory (UT). Data were collected using a modified version of the Attitude Towards Patients with Epilepsy (ATPE) scale to evaluate teachers’ preparedness, attitudes, and systemic support for students with epilepsy. Results: The study revealed significant knowledge deficits and prevalent misconceptions about epilepsy among teachers. While 84% of participants reported awareness of epilepsy, many lacked detailed knowledge about its causes, symptoms, and modern treatments. Misconceptions included beliefs that epilepsy is caused by supernatural forces or is transmissible through physical contact. Attitudinal analysis showed mixed perspectives, with 40.5% of teachers agreeing that epileptic students should be taught in separate classrooms. The dropout rate among epileptic students was documented at an alarming 55%, primarily due to stigma, health-related challenges, and inadequate educational support. Conclusion: This study highlights the urgent need for comprehensive teacher training programs, awareness campaigns, and policy-driven interventions to address stigma, bridge knowledge gaps, and promote inclusive education. By fostering a supportive environment, these measures can improve academic and social outcomes for students with epilepsy in the J&K UT and similar global contexts.